Perancangan Website User Interface Design Pada Laundry Ruru Sapatu Ciamis Menggunakan Metode Kansei Engineering - Rizki Firman Fauzi; Sidiq, Maulana; Mulyana, Dadan (Jurnal Mahasiswa Sistem Informasi Galuh, 2024)
This study applies the Kansei Engineering method in designing a website user interface design with Kansei Engineering Type I. This design aims to design a website interface in one of the shoe laundry service sectors based on the emotional factors of website users. In this study, the design of the website interface only applies to Ruru Sapatu Ciamis. Ruru Sapatu Ciamis is one of the shoe laundry service sectors in the Ciamis area that has been established since 2020 and has various types of shoe washing. Through a research method in accordance with Kansei Engineering Type I, there are several stages in Kansei Engineering Type I used in this study starting with determining the strategy, collecting kansei words, compiling a semantic differential scale, determining specimens and classification of design elements, determining participants and distributing questionnaires, collecting questionnaire data, using multivariate statistical analysis, namely correlation coefficient analysis, principal components, principal factor analysis and partial Least Square and the final stage of design proposal recommendations. The final result of this study is the emergence of a design proposal matrix that is processed into a design sketch and recommendations for the Ruru Sapatu Ciamis website interface based on the Kansei Engineering method with a design concept that has the highest value from all participants and all the kansei words used, namely a design concept with a value of 0.9 proportional kansei words.